2018
DOI: 10.1371/journal.ppat.1007115
|View full text |Cite
|
Sign up to set email alerts
|

A cell-based infection assay identifies efflux pump modulators that reduce bacterial intracellular load

Abstract: Bacterial efflux pumps transport small molecules from the cytoplasm or periplasm outside the cell. Efflux pump activity is typically increased in multi-drug resistant (MDR) pathogens; chemicals that inhibit efflux pumps may have potential for antibiotic development. Using an in-cell screen, we identified three efflux pump modulators (EPMs) from a drug diversity library. The screening platform uses macrophages infected with the human Gram-negative pathogen Salmonella enterica (Salmonella) to identify small mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 80 publications
5
83
0
Order By: Relevance
“…However, others have shown that TolC is required, and therefore active, for intracellular growth of S . Tm 35,36 . We therefore reasoned that OM permeability, and not reduced efflux, contributes to metergoline activity in macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have shown that TolC is required, and therefore active, for intracellular growth of S . Tm 35,36 . We therefore reasoned that OM permeability, and not reduced efflux, contributes to metergoline activity in macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular pathogens often occupy niches that are difficult to recapitulate in vitro; thus, we and others have developed fluorescence, luminescence, and colorimetric-based screening assays with readouts that approximate bacterial viability when compared to traditional cfu counting methods 36,5356 . Here we describe a macrophage-based chemical screen specific for intracellular S .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, macAB is important for S . Typhimurium replication in macrophages [ 38 , 56 ], a niche where PhoP/Q signaling is active and important for Salmonella survival [ 55 , 61 ]. In addition to the different Salmonella isolates used across studies, our results suggesting PhoP promotes macAB transcription may arise from differences in experimental conditions, the importance of regulatory kinetics such as PhoP turnover [ 38 ], changes in ribosomal RNA levels in response to low magnesium [ 84 ], or coordinated activity with other transcriptional regulators [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that S. Typhimurium ST19 strains 14028S and SL1344 with deletions of macAB replicate poorly within mouse macrophages [38,56]. We infected the murine RAW264.7 macrophage cell line with a range of our marker-less macAB mutants to assess Salmonella intracellular replication.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Intracellular pathogens often occupy niches that are difficult to recapitulate in vitro; thus, we and others have developed fluorescence, luminescence, and colorimetric-based screening assays with readouts that approximate bacterial viability over traditional cfu counting methods 44-48 . Here we describe a macrophage-based chemical screen specific for intracellular S .…”
Section: Discussionmentioning
confidence: 99%